AMANAT YANG TERKANDUNG DALAM NOVEL “CATATAN HATI SEORANG AYAH “KARYA REMBULAN RATRI - Gowasa, Hilda Selvin Yanti (FAGURU: Jurnal Ilmiah Mahasiswa Keguruan, 2024)
The aim of the research is to describe the written and implied message in the novel "Notes of a Father's Heart" by Rembulan Ratri. This type of research is Qualitative Research with a Content Analysis research method. The object of this research is the novel "Notes of a Father's Heart" by Rembulan Ratri. The data collection technique is a documentation technique using written sources. There are four data analysis techniques, namely, 1. Data collection, 2. Data reduction, 3. Data presentation, 4. Drawing conclusions. The results of this research show that in the novel "Notes of a Father's Heart" by Rembulan Ratri, there is an implicit (implicit) message and an explicit (explicit) message. The type of mandate that dominates the two types of mandate is a written (explicit) mandate. 4 implicit (implicit) messages and 12 explicit (explicit) messages. The suggestions put forward by the researcher are 1) For Indonesian language teachers, it should be used as learning material in Indonesian language subjects, 2) Students should be able to understand the messages in the novel. can be used as motivation for everyday life, 3) For readers, they should be able to understand the message or message contained in the novel, so that the message or message can be guided and carried out in everyday life, and 4) For future researchers, this author does not free from shortcomings and errors, therefore the author hopes for other researchers to continue this research, especially the mandate contained in the novel and carry out this research with a wider range of material.